PENGARUH PROFITABILITAS, KEPUTUSAN INVESTASI, KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia periode 2011 - 2015) - Setiono, Dedi Bangun; Susetyo, Budi; Mubarok, Abdullah (PERMANA, 2017)
This study aims to examine the effect of profitability, investment decisions, dividend policy and debt policy to corporate values simultaneously and partially. The population of this study is a manufacturing company of the consumer goods industry sector listed on the Indonesia Stock Exchange. Sampling method used is purposive sampling method. Samples were collected from 8 manufacturing companies of the consumer goods industry sector listed on the Indonesia Stock Exchange during the period 2011-2015. Data collection method in this research is documentation. While the data analysis method used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, F test, t test and coefficient of determination test. Based on the results of multiple regression analysis shows that profitability, investment decisions, dividend policy and debt policy have a significant effect on corporate value with a significance value of 0.000. Profitability significantly partially affect the value of the company with a significance value of 0.000. Investment Decision significantly influence partially to company value with its significan value of 0.000. The dividend policy has no significant effect partially on the value of the company with its significant value of 0.660 and the debt policy has a significant effect partially on the value of the firm with its significance value of 0.001.  Keywords: profitability, investment decisions, dividend policy, debt policy, corporate value